2014
DOI: 10.1002/lary.24990
|View full text |Cite
|
Sign up to set email alerts
|

Relation of mean platelet volume and red blood cell distribution width with epistaxis

Abstract: The results of this study showed a clinical finding of lower mean platelet volume and red blood cell distribution levels in epistaxis. These findings could be beneficial in new investigations into epistaxis mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
(53 reference statements)
1
11
2
3
Order By: Relevance
“…25 Also Kemal et al studied MPV and RDW levels of patients complaining from recurrent epistaxis in adults and detected lower MPV and RDW levels. 4 In our study MPV and RDW values were higher than those of control group but this difference was not statistically significant. The different results may be explained by younger age of our study population and difference of patient selection criteria.…”
Section: Red Blood Cell Distribution Width (Rdw)contrasting
confidence: 69%
See 2 more Smart Citations
“…25 Also Kemal et al studied MPV and RDW levels of patients complaining from recurrent epistaxis in adults and detected lower MPV and RDW levels. 4 In our study MPV and RDW values were higher than those of control group but this difference was not statistically significant. The different results may be explained by younger age of our study population and difference of patient selection criteria.…”
Section: Red Blood Cell Distribution Width (Rdw)contrasting
confidence: 69%
“…In healthy individuals with an unremarkable CBC, MPV can be useful in predicting an increased bleeding risk. [4][5][6] Red blood cell distribution width (RDW) is a routine component of the CBC. It means the variability of the size of the red blood cells in the blood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, We applaud the work by Kemal et al, 1 in their well-presented article. The authors found lower mean platelet volume (MPV) and red blood cell distribution (RDW) levels in epistaxis.…”
Section: In Reference To Relation Of Mean Platelet Volume and Red Blomentioning
confidence: 96%
“…RDW başta anemi olmak üzere birçok hematolojik hastalığın ayırıcı tanısında kullanılmaktadır. Son yıllarda RDW de aynı MPV gibi birçok tromboembolik ve hemorajik hastalıkta MPV araştırılmıştır (5,7).…”
Section: Introductionunclassified